L’amour et la révolte dans Le couteau sur la table, roman de Jacques Godbout - Mojžíšová, Natalie (Romanica Silesiana, 2020)
The novel depicts the relationship of a young couple living in Montreal. The poetics of the text not only provides the reader with an unusual aesthetic experience but also reveals interesting details about life in Canada in the 1960s. We will introduce the main characters of the novel and focus on some of its aspects, especially those moments where the political situation, whether historically distant or recent, is reflected in the life of modern society. The sixties of the twentieth century were imbued with a desire to resist authority which was lived collectively and also as an individual issue. In the novel, the theme of revolt is portrayed on both these levels, but it shows that it is not always easy to realize one’s ideas in practice. The structure of the novel which refers to the influence of nouveau roman is composed of fragmentary narrative, repetitive allusions and unfinished sentences. Using all these techniques Jacques Godbout has created a captivating text, fascinating especially by its disquieting dynamics.